![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(M=5xy-\dfrac{2}{3}xy+xy\)
\(M=\dfrac{16}{3}xy\)
b) \(N=3xy^2-\left(-5xy^2\right)-3xy^2\)
\(N=3xy^2+5xy^2-3xy^2\)
\(N=5xy^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài làm
1.
a) 5x.3xy2
= 15x2y2
b) ( -2/3 xy2z )( -3x2y)2
= ( -2/3xy2z)( 9x4y2 )
= -6x5y4z
2)
a) M = P + Q = ( 3x2y - 2x + 5xy2 - 7y2 ) + ( 3xy2 - 7y2 - 9x2y - x - 5 )
= 3x2y - 2x + 5xy2 - 7y2 + 3xy2 - 7y2 - 9x2y - x - 5
= ( 3x2y - 9x2y ) + ( 5xy2 + 3xy2 ) + ( -2x - x ) + ( -7y2 - 7y2 ) - 5
= -6x2y + 8xy2 - 3x -14y2 - 5
Vậy M = P + Q = -6x2y + 8xy2 - 3x -14y2 - 5
b) M = Q - P = ( 3xy2 - 7y2 - 9x2y - x - 5 ) - ( 3x2y - 2x + 5xy2 - 7y2 )
= 3xy2 - 7y2 - 9x2y - x - 5 - 3x2y + 2x - 5xy2 + 7y2
= ( -3x2y - 9x2y ) + ( 3xy2 - 5xy2 ) + ( 2x - x ) + ( -7y2 + 7y2 ) - 5
= -11x2y - 2xy2 + x - 5
Vậy M = Q - P = -11x2y - 2xy2 + x - 5
![](https://rs.olm.vn/images/avt/0.png?1311)
a) A = -2xy2 + 3xy + 5xy2 + 5xy + 1
A = (-2xy2 + 5xy2) + (3xy + 5xy) + 1
A = 3xy2 + 8xy + 1
b) Với x = \(\frac{-1}{2}\) ; y = -1
Thì A = 3xy2 + 8xy + 1
A = \(3.\frac{-1}{2}.1^2+8.\frac{-1}{2}.1+1\)
A = \(-\frac{9}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, B = ( 5 . 1 .(-3) ) (x.x.x ) ( y2 .y.y2 )
B = -15x3y5
b, Thay x=1 , y= -1
Ta có : B = -15 . 13.(-1)5
B = -15 .1.(-1)
B = 15
Vậy B = 15 tại x=1 , y=-1
HT
![](https://rs.olm.vn/images/avt/0.png?1311)
\(=6x^3y^3-x^4y-\dfrac{7}{2}xy^2-5x^4y-6x^3y^3\)
\(=-\dfrac{7}{2}xy^2-6x^4y\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1.
a)\(\left(\dfrac{1}{2}\cdot\left(-2\right)\cdot\dfrac{-1}{3}\right)\cdot\left(x^2\cdot x^2\cdot x^2\right)\cdot\left(y^2\cdot y^3\right)\cdot z\)
\(\dfrac{1}{3}x^6y^5z\)
Deg=12
![](https://rs.olm.vn/images/avt/0.png?1311)
\(5x^2y-3xy+\frac{1}{2}x^2y-xy+5xy-\frac{1}{3}x+\frac{1}{2}+\frac{2}{3}x-\frac{1}{4}\)
\(=\left(5x^2y+\frac{1}{2}x^2y\right)+\left(-3xy-xy+5xy\right)+\left(-\frac{1}{2}x+\frac{2}{3}x\right)+\left(\frac{1}{2}-\frac{1}{4}\right)\)
\(=\frac{11}{2}x^2y+xy+\frac{1}{6}x+\frac{1}{2}\)
\(B=2xy^2+xy\)
B=2xy2+xy